Potential effect of ethanolic extract of Abutilon indicum (L.) against acetic acid induced ulcerative colitis in albino rats - Shoba S.; Ishwarya M. P.; Kiruthika K.; Priyatharshini A.; Rathipriya J.; Sundaramahalingam S. (International Journal of Basic & Clinical Pharmacology, 2026)
Background: Ulcerative colitis (UC) is a chronic, relapsing inflammatory disorder of the colon characterized by mucosal inflammation, ulceration, and disruption of intestinal homeostasis Abutilon indicum (L.), a traditionally used medicinal plant in Ayurvedic and folk medicine, has been reported to possess various pharmacological activities including anti-inflammatory, antioxidant, analgesic, and wound healing effects. However, its potential role in the management of ulcerative colitis remains inadequately explored and requires scientific validation. Methods: Animals were treated for 11 days in different groups. Group I received normal saline, Group II received distilled water, Group III received sulfasalazine, and Groups IV & V received Abutilon indicum extract at two doses. On day 8, ulcerative colitis was induced in Groups II-V using 4% acetic acid administered rectally. On day 11, animals were anesthetized, blood samples were collected, and colon tissues were preserved for analysis (cytokine study and histopathology). Results: The study showed that ethanolic extract of Abutilon indicum leaves has significant anti-ulcerative colitis activity against acetic acid-induced colitis. Both doses (250 mg/kg and 500 mg/kg) were effective, but 500 mg/kg showed better results. This effect was confirmed by reduced inflammatory markers (TNF-a, IL-6), decreased colon weight-length ratio, and improved histopathological findings. Conclusions: The findings suggest that the plant possesses promising anti-colitic potential and may serve as a natural therapeutic candidate for the management of ulcerative colitis. Further studies are warranted to isolate the active constituents, elucidate the underlying molecular mechanisms, and establish its clinical efficacy and safety.